Clinical correlates of erectile dysfunction among male patients on methadone maintenance therapy (MMT) in Kuala Lumpur - Nik Jaafar, Nik Ruzyanei; Mislan, Noormazita; Baharudin, Azlin; Ibrahim, Normala; Zakaria, Hazli; Abdul Aziz, Salina; Sidi, Hatta (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Introduction: Sexual dysfunction is common but not often assessed in the routine clinical care among males on opiate substitute treatment. Objective: To determine the association between clinical variables and erectile dysfunction (ED) among men on methadone maintenance therapy (MMT). Methods: A cross-sectional study involving 108 participants who attended the Drug Clinic, Hospital Kuala Lumpur. The instruments used include the Structured Clinical Interview for DSM-IV Axis-I Disorder (SCID-I),Beck Depression Inventory (BDI) and International Index of Erectile Function-15 (IIEF-15). Results: Concurrent heroin abuse was significantly associated with presence of ED (p=0.024). Treatment factors including methadone dose and duration of methadone treatment were not significantly associated with ED. Conclusion: Education on sexual dysfunction as a potential adverse effect and its association with illicit heroin use should be considered in the doctor-patient consultation to encourage treatment adherence and abstinence from heroin.